IMF Research Bulletin, Fall 2017. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 2017)
The Fall 2017 IMF Research Bulletin includes a Q and A article covering "Seven Questions on the Globalization of Farmland" by Christian Bogmans. The first research summary, by Manmohan Singh and Haobing Wang is "Central Bank Balance Sheet Policies: Some Policy Implications." The second research summary is "Leaning Against the Windy Bank Lending" by Giovanni Melina and Stefania Villa. A listing of new IMF Working Papers and Staff Discussion Notes is featured, as well as new titles from IMF Publications. Information on IMF Economic Review is also included.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet